Under pressure ; Cool and light [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Interview with the gold hundred and PCGG officials on the burried treasures at Bastion de San Lorenzo, Fort Santiago. Present the sentimental music of Kalapana and their singing career and Kenny Rankin.
Under pressure (13 min.) -- Cool and light (22 min.)
VHS
Keywords: Marcos, Ferdinand e., 1917-1989.; Rankin, Kenny -- Interviews; Kalapana (Singing group).; Treasure trove -- Asia